Approach to enhancing myoblast cell proliferation through plasma jet stimulation for the design of lab-grown meat - Natpaphan Yawut; Komgrit Leksakul; Norrapon Vichiansan; Dheerawan Boonyawan; Thippawan Mekwilai (Journal of Agriculture and Food Research, 2025)
This study investigates the optimal parameters for stimulating myoblast cell proliferation using cold plasma technology, providing foundational insights for lab-grown meat research. A full factorial experimental design was employed to evaluate the effects of plasma power level, electrode spacing, gas flow rate, and treatment time on cell proliferation. A total of 37 experiments, including two replicates and a center point, identified optimal conditions: 0.28 W power, 3 L/min gas flow rate (0.63 L/min O₂ and 2.34 L/min N₂), 1-min treatment time, and 2 cm electrode gap. These conditions significantly enhanced myoblast cell proliferation, with a minimum increase of 9.54 % compared to the control group, as confirmed by fluorescence morphology. Reactive oxygen and nitrogen species (RONS) generated during plasma treatment were found to influence intracellular signaling, with nitrogen species promoting proliferation and atomic oxygen inducing cell stress. Gene expression analysis at 24 h revealed upregulation of PRDM2 and GAPDH, key regulators of cell development and proliferation. This research highlights the potential of cold plasma as a novel, resource-efficient method for scaling myoblast cell numbers, contributing to sustainable alternative protein production. The findings have implications for addressing food security, reducing reliance on livestock farming, and expanding knowledge across biomedical and biotechnological applications.